The Relevance of Lev Vygotsky's Constructivist Theory to the Islamic Religious Education Learning System in Indonesia - Ariansyah, DD Alija (Mudir : Jurnal Manajemen Pendidikan, 2023)
This research discusses the relationship of Lev Vygotsky's constructivist theory to Islamic Religious Education (PAI) learning in Indonesia. In some cases, it is still found that the implementation of PAI learning is carried out through the indoctrination method. Students are given a "black and white" understanding of religion. This conservative approach is carried out to persuade them to obey and comply with religion without any effort to raise critical awareness. Because of this, mechanical tasks are often given to students without supporting the learning process at school, or even just mechanical tasks that are outside the context of basic abilities and competency standards. In more detail, this research examines what aspects of Lev Vygotsky's constructivist thinking are contextual to PAI learning practices in Islamic educational institutions in Indonesia. The research method in this research uses a qualitative descriptive approach with a literature review. The results of the analysis of Vygotsky's constructivism theory and the Islamic learning system have a relevant relationship in the learning process. Evidence connecting Lev Vygotsky's constructivist theory with the PAI learning system in Indonesia can be seen from the implementation of a collaborative approach in PAI learning, where the teacher acts as a mediator in helping students understand religious concepts through interaction and discussion. Apart from that, the use of language as a mediating tool in understanding religious concepts also reflects an important concept in Vygotsky's thinking about the role of language in learning.